Influence of electromagnetic stirring (EMS) on the microstructure and mechanical property of Incoloy825 superalloy. (April 2017) - Wang, Fei; Wang, Engang; Zhang, Lintao; Jia, Peng; Wang, Tao
Abstract: We experimentally investigate the influence of the electromagnetic stirring (EMS) on the microstructure and the mechanical properties of Incoloy825 superalloy. Three trails of experiments with different values of the EMS alternating current ( I = 0, 150 and 300 A, respectively), however with identical EMS frequency ( f = 5 Hz), were conducted. We figure out that the equiaxed grain region is increased and the average grain size is decreased whilst EMS is applied. The application of EMS can also decrease the total number of TiN, especially for the inclusion in large scales (>2 μm). The values of the yield strength, the ultimate tensile strength and the elongation of Incoloy825 superalloy specimens are also increased whilst EMS is applied.